Polarizable Simulations with Second order Interaction Model (POSSIM) force field: Developing parameters for protein side-chain analogues - Li, Xinbi (2013)
A previously introduced POSSIM (POlarizable Simulations with Second order Interaction Model) force field has been extended to include parameters for small molecules serving as models for peptide and protein side-chains. Parameters have been fitted to permit reproducing many-body energies, gas-phase dimerization energies and geometries and liquid-phase heats of vaporization and densities. Quantum mechanical and experimental data have been used as the target for the fitting. The POSSIM framework combines accuracy of a polarizable force field and computational efficiency of the second-order approximation of the full-scale induced point dipole polarization formalism. The resulting parameters can be used for simulations of the parameterized molecules themselves or their analogues. In addition to this, these force field parameters are currently being employed in further development of the POSSIM fast polarizable force field for proteins.